Structural determinants of inequalities in untreated dental caries in the Global Burden of Disease Study - Orlando Luiz do Amaral Junior; Maria Laura Braccini Fagundes; Fernando Neves Hugo; Nicholas J. Kassebaum; Jessye Melgarejo do Amaral Giordani (PLoS ONE, 2025)
Introduction Untreated dental caries remains a significant global public health challenge, disproportionately affecting vulnerable populations and highlighting inequalities in health systems worldwide. Examining its distribution across diverse contexts is essential for guiding targeted interventions, informing public policies, and allocating resources more effectively. This study aims to provide a comprehensive global assessment of the distribution of untreated dental caries in 204 countries and territories, spanning the years 2000, 2010, and 2019, by dimensions of structural determinants of health. Methods This study employs an ecological design. This analysis describes the incidence, prevalence and years lived with disability (YLDs) due to untreated dental caries in permanent and deciduous teeth by structural determinants of health (dimensions of governance, macroeconomic policy, social policy, public policies and culture/societal values), for 204 countries and territories. Estimates of untreated caries in deciduous teeth by structural determinants were reported for children under 5 years of age, whereas estimates in permanent teeth were described for adolescents and adults aged between 15 and 49 years. Estimates were retrieved from the Global Health Data Exchange. Results There was a gradient of inequality between countries in terms of prevalence, YLDs, and the incidence of overt untreated caries. Countries that had better structural indicators had lower mean prevalence of untreated caries in primary teeth. In the permanent dentition, between-countries inequalities were not identified. Additionally, the mean prevalence was stable from 2010 to 2019. Conclusions This study revealed possible cross-country inequalities in the burden of untreated caries in deciduous teeth that persisted over one decade. More developed countries experienced less disease burden. These findings show the need for targeted interventions to address the uneven burden of untreated dental caries worldwide. Clinical significance This study underscores the need for targeted global health policies to reduce untreated dental caries, especially in countries with lower structural health determinants, highlighting cross-country inequalities in disease burden and the importance of addressing these disparities in both primary and permanent dentition.